Elective lower limb orthopedic arthroplasty surgery in patients with pulmonary hypertension. (25th March 2022) - Wardle, Mikaela; Nair, Amanda; Saunders, Sarah; Armstrong, Iain; Charalampopoulos, Athanasios; Elliot, Charlie; Hameed, Abdul; Hamilton, Neil; Harrington, John; Keen, Carol; Lewis, Robert; Sabroe, Ian; et al.
Abstract: Patients with pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension (PH) are at increased risk when undergoing anesthesia and major surgery. Data on outcomes for elective orthopedic surgery in patients with PH are limited. A patient pathway was established to provide access to elective lower limb arthroplasty. This included assessment of orthopedic needs, fitness for anesthesia, preoperative optimization, and intra‐ and postoperative management. Patient data were retrospectively retrieved using patient's hospital records. Between 2012 and 2020, 29 operations (21 total hip replacements [THRs], 7 total knee replacements [TKRs], 1 total hip revision) were performed in 25 patients (mean age: 67 years). Perioperatively, 72% were treated with low‐dose intravenous prostanoid. All had arterial lines, and central access and perioperative lithium dilution cardiac output monitoring was used in 86% of cases. Four patients underwent GA, 21 spinal anesthesia, and 4 CSE anesthesia. Supplemental nerve blocks were performed in all patients undergoing general, and 12 of 21 undergoing spinal anesthesia. All were managed in high dependency postoperatively. Hospital length of stay and complication rates were higher than reported in non‐PH patients. Perioperative complications included hypotension requiring vasopressors ( n  = 10), blood transfusion ( n  = 7), nonorthopedic infection ( n  = 4), and decompensated right heart failure ( n  = 1). There was no associated mortality. All implants were functioning well at 6 weeks and subsequent follow‐up. EmPHasis‐10 quality of score decreased by 5.5 (±2.1) ( p  = 0.04). A dedicated multiprofessional pathway can be used to safely select and manage patients with PH through elective lower limb arthroplasty.